Deformation and failure characteristics of high-speed tunnels in complex karst areas: a case at the Qilinguan tunnel - Hu, Changgeng (Frontiers in Earth Science, 2023)
The construction of expressway tunnels in karst areas faces many challenges under complex geological conditions. It is of great scientific and engineering significance to study the deformation and failure laws of tunnels and surfaces. Taking the Qilinguan tunnel of the Hubei Expressway as an example, the deformation and failure laws of the tunnel are analyzed when the tunnel passes through the complex karst area. The composition of karst water and surrounding rock was analyzed by inductively coupled plasma mass spectrometry and XRD, and the compression-shear failure model of tunnels in karst areas was proposed according to the regional hydrological and geological conditions. It was found that the thickness of the protective layer and the water pressure were the main factors affecting the deformation and failure of the surrounding rock in this area, and the treatment scheme of this project was put forward accordingly. The geological characteristics of karst areas were explored by advanced geological prediction and advanced geological drilling. The primary support is provided by a steel arch and advanced small pipe grouting. The composite lining is composed of shotcrete as the primary support and molded concrete as the secondary lining. The primary support structure of the flexible support system is adopted in the design to give full play to the bearing capacity of the surrounding rock. After the support measures were adopted, the trend of settlement change gradually slowed down, indicating that the support measures were effective.